Forklift truck selection using TOPSIS method - Průša, Petr; Jovčić, Stefan; Němec, Vladimír; Mrázek, Petr (My University, 2018)
Forklift trucks have a very important role in manipulating goods in the logistics industry and, therefore, companies must pay special attention to them. There are different types of forklifts and when make a decision, companies select some of the important criterias on the basis of which different forklift trucks will be chosen. The subject of research paper is the selection of a forklift truck for manipulating goods in the warehouse. A TOPSIS method was used to select the forklift truck, a well-known method of multi-criteria analysis, which has been proven in practice as a very efficient and reliable when deciding. The main result of this paper is determining the best alternative that would be the optimal solution for the logistics company. The decision was made on the basis of observation of four forklift trucks with five characteristics of different sizes.
Výběr vozíku pomocí metody TOPSIS
Keywords: TOPSIS method; multi-criteria analysis; forklift; logistics; investment; Metoda TOPSIS; multikriteriální analýza; vysokozdvižný vozík; logistika; investice